Single‐Trajectory Multiple‐Target Deep Brain Stimulation for Parkinsonian Mobility and Cognition. Issue 3 (22nd November 2021) - Sasikumar, Sanskriti; Cohn, Melanie; Harmsen, Irene E.; Loh, Aaron; Cho, Sang Soo; Sáenz‐Farret, Michel; Maciel, Ricardo; Soh, Derrick; Boutet, Alexandre; Germann, Jürgen; Elias, Gavin; Youm, Ariana; et al.
Abstract: Background: Deep brain stimulation (DBS) of the nucleus basalis of Meynert (NBM) is an emerging target to potentially treat cognitive dysfunction. Objectives: The aim of this study is to achieve feasibility and safety of globus pallidus pars interna (GPi) and NBM DBS in advanced PD with cognitive impairment. Methods: We performed a phase‐II double‐blind crossover pilot trial in six participants to assess safety and cognitive measures, the acute effect of NBM stimulation on attention, motor and neuropsychological data at one year, and neuroimaging biomarkers of NBM stimulation. Results: NBM DBS was well tolerated but did not improve cognition. GPi DBS improved dyskinesia and motor fluctuations ( P = 0.04) at one year. NBM stimulation was associated with reduced right frontal and parietal glucose metabolism ( P < 0.01) and increased low‐ and high‐frequency power and functional connectivity. Volume of tissue activated in the left NBM was associated with stable cognition ( P < 0.05). Conclusions: Simultaneous GPi and NBM stimulation is safe and improves motor complications. NBM stimulation altered neuroimaging biomarkers but without lasting cognitive improvement. © 2021 International Parkinson and Movement Disorder Society